The system for the martial arts training analysis - Lach, P.; Lach, P.; Busko, K.; Staniak, Z.; Mazur Rózycka, J.; Gajewski, J.; Michalski, R. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: One of the methods of assessing the physical fitness, strength and athletes` speed in combat sports is the analysis of combat simulation. The purpose of this study was designing a method and tools for measuring punching force using accelerometers. The essence of the project was to build a simple, versatile boxing training simulator that allows measuring a blowing and kicking force as well as reaction time of athletes. Methods: The new system was designed to measure and analyze the mechanical characteristics of punching and kicking with upper and lower limbs in a boxing bag. System consists of a punching bag with embedded accelerometers, four signal lights attached to it and software. The punching bag is 170 cm high and weights 41 kg. The bag hangs vertically on the winch. It`s mounted on the ropes that stabilize the device. Winch allows adjusting the suspension height of the bag. Acceleration transducers are placed inside the bag, which allow calculation of dynamics during punching the bag. The system runs with software that integrates all the parts and it allows controlling data acquisition and processing. The software calculates the strength of the blow, the point of a force application and its direction, energy of a hit and time reaction, defined as the time between the light signal and registering a punch. The force of a blow is calculated using the acceleration data. Results: of testing the system The system was tested and results show that the average, relative error of force calculation amounts to 3%. The error of acceleration measures is less than 1%. The average, relative error of calculation the punching place on the boxing bag is 2%. Conclusion: With using this boxing simulator, the intensity of training can be controlled more precisely, due to the possibility of setting e.g. time intervals between consecutive blows or sequence of delivered punches. The versatility of the software makes the system a good tool for practical application in training martial arts.